A prospective study on the effects of glucosamine hydrochloride and chondroitin sulfate combination on systemic inflammation markers in patients with knee osteoarthritis (report 1) - A. M. Lila; E. A. Taskina; L. I. Alekseeva; N. G. Kashevarova; E. A. Strebkova; N. M. Savushkina; N. M. Savushkina; T. A. Korotkova; A. S. Avdeeva; E. Yu. Samarkina; M. E. Diatroptov (Современная ревматология, 2025)
Objective: to assess the effect of a combination of glucosamine hydrochloride (GH) 500 mg and chondroitin sulfate (CS) 500 mg (Artra®) on systemic inflammation markers in patients with knee osteoarthritis (KOA).Material and methods. The study included 70 patients with a confirmed diagnosis of KOA stage II–III and walking pain ≥4 points on a numerical rating scale (NRS). Study duration was 3 months. All patients received Artra® and, if necessary, topical nonsteroidal anti-inflammatory drugs (NSAIDs). Treatment efficacy was evaluated by changes in pain according to NRS, the WOMAC index, and patient global assessment of health status (PGA) using a visual analogue scale (VAS). C-reactive protein (CRP) levels were measured during visits 1 and 3 in all patients; 40 patients also had their serum levels of 17 cytokines, chemokines, and growth factors assessed.Results and discussion. After 3 months of treatment, there was a rapid and significant decrease in pain according to NRS (from 5 [5; 6] to 3 [2; 4] points), pain on WOMAC (from 9 [7; 11] to 5 [3; 8] points), stiffness on WOMAC (from 4 [3; 5] to 3 [1; 4] points), improvement in physical function on WOMAC (from 36 [24; 41] to 23.5 [12; 32] points), and PGA (from 50 [50; 70] to 65 [58; 75] mm), p<0.0001 for all comparisons. A decrease was also observed in the number of patients with clinically apparent synovitis (p=0.04) and limited range of motion in the knee joint (p<0.0001). A significant advantage of the GH and CS combination is its impact on inflammatory markers – in particular, a reduction in tumor necrosis factor alpha (TNFα) levels (p=0.04).Conclusion. In patients with KOA, Artra® demonstrated a rapid symptomatic effect, which continued to increase over the 3-month observation period. Our study confirmed the more subtle molecular mechanisms behind the beneficial effects of the GH and CS combination through suppression of inflammatory mediator production, particularly TNFα. These findings suggest a systemic effect of the drug, making it particularly promising for treating patients with comorbidities.